Analisis Penerimaan Pengguna BSE dengan Pendekatan Technology Acceptance Model di Kabupaten Kulon Progo - Chris Agung Pramudi; Ahmad Ashari; Selo Sulistyo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Aspects of user acceptance become one the main factors for success of the application of information technology. Use of Electronic School Book (BSE) led to a transformation of the how getting a book and learning from the manual into an electronic system, which lead to the attitude and behavior of the user to accepting and use it for real. This study analyzes user acceptance BSE in the Regency of Kulon Progo, measured from the level of user acceptance.Technology Acceptance Model (TAM) is used as a framework for modeling acceptance BSE. Model generated identifies three exogenous variables are: ease of use, usefulness, and behavioral intention to use and 4 endogenous variables are: subjective norm, system relevance, accessibility quality and computer self-efficacy. The model was analyzed using the Structured Equation Modeling (SEM) with AMOS 21 program.The results showed that the TAM model to explain the factors that influence user acceptance BSE. Based on a sample of 167 respondents that are teachers as BSE users, of the total 10 hypotheses suggests that the accessibility variable quality not significantly affect the perception of usefulness and perceived ease of use of BSE. BSE Actual use is low, need to encourage the willingness to use BSE with respect to user acceptance variables.